The Australian Leadership Reader : Six Leading Australians and Their Stories. - Sykes, Helen (Australian Academic Press, 2006)
Appropriate for use in Australian secondary and undergraduate studies, this unique book does not try to define leadership, but instead encourages the reader to fulfil that task themselves through a series of short essays on the personal and professional life of some contemporary Australians recognised nationally as aspiring leaders in their fields.